Capturing the Voices of Learners from Non-Western and Indigenous Cultures: Links to Learning in Adulthood - Thomas Della Porta; Rosemary S. Caffarella (Adult Education Research Conference, 2010)
Reviewed in this roundtable session are different frames of knowing and learning from non-western and indigenous cultures, and how these cultures contrast to those of western societies. A discussion follows of what these differences mean for teaching and organizing programs for adult learners.